Prvi pesemski cikli slovenskih pesnic - Žerjal-Pavlin, Vita (Jezik in slovstvo, 2012)
After Josipina Turnograjska's cyclic poem Always Beautiful Is Nature from 1851, Luiza Pesjak and Pavlina Pajk were next among the first Slovene women poets to compose lyrical cycles in the second half of the 19th century. In so doing, they relied on both foreign and domestic examples of cyclic poems that were initially inspired by Prešeren's cycles. In part, they used typical themes of the age (patriotism, travel impressions, seasons of the year), but, in the extended cyclic form, they also presented a specifically female experience (attitude to marriage, motherhood, their own lives). Since both authors are well known, perhaps even primarily known, as narrative writers, it is not surprising that they chose a syntagmatic poem cycle that allows modification of the lyrics into a narrative structure. The fact that they chose the rational form of the cycle also reflects their literary ambition.
Keywords: Turnograjska, Josipina, 1833-1854; Pesjak, Luiza, 1828-1898; Pajk, Pavlina, 1845-1901; Slovene literature; slovenska književnost; slovenska poezija; slovenske pesnice; pesemski cikel; tematologija; materinstvo; domoljubje; potopisni cikel; letni časi; 19.st.